Editorial - Antonios Giannopoulos (Journal of Tourism, Heritage & Services Marketing)
We are pleased to present the twenteeth publication of JTHSM (volume 10, issue 2), the last issue in its tenth year of publication. In previous issues, this journal presented original refereed papers, both conceptual and research-based, focused on various topics of tourism, heritage, and services with an emphasis on marketing and management. Volume 10, issue 2 focus on furthering the journal’s scope and consolidating its position in both conceptual developments and practical applications in tourism, heritage and services through publication of nine quality manuscripts that underwent rigorous double-blind reviewing: seven exciting full papers.